2020
DOI: 10.1111/jvp.12859
|View full text |Cite
|
Sign up to set email alerts
|

Oral doxycycline pharmacokinetics: Lambs in comparison with sheep

Abstract: The pharmacokinetics of doxycycline was investigated in lactating sheep and lambs after oral administration at a dose of 10 mg/kg. Concentrations in plasma and milk were assayed with HPLC‐PDA analysis. Doxycycline penetrates into the milk, and levels (0.38 ± 0.21 μg/ml) were found 0.5 hr after the treatment. The results suggest that the lambs can be exposed to doxycycline by suckling milk from their treated mothers. Population pharmacokinetic analysis showed a positive relationship between age, which reflects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Furthermore, previous investigations revealed differences in the pharmacokinetics of doxycycline between young calves and mature ruminants [ 28 ]. In a comparative study that was carried out on the pharmacokinetics of orally administered doxycycline in lambs and lactating ewes, it was observed that the values of clearance were significantly higher in adult sheep and that the plasma concentration was higher in lambs [ 29 ]. However, in calves, it was observed that after intravenous doxycycline administration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous investigations revealed differences in the pharmacokinetics of doxycycline between young calves and mature ruminants [ 28 ]. In a comparative study that was carried out on the pharmacokinetics of orally administered doxycycline in lambs and lactating ewes, it was observed that the values of clearance were significantly higher in adult sheep and that the plasma concentration was higher in lambs [ 29 ]. However, in calves, it was observed that after intravenous doxycycline administration.…”
Section: Discussionmentioning
confidence: 99%
“…Although doxycycline has broad spectrum activity, it is particularly beneficial in treating infections involving atypical bacteria and bacteria that lack a cell wall, such as Mycoplasma and Rickettsia species (Holmes and Charles 2009). Both oral and parenteral administration have been described in domestic sheep, goats, and cattle (Meijer et al 1993; Ole-Mapenay and Mitema 1997; Castro et al 2009; Castro Robles et al 2012; Mileva et al 2020). Tetracycline antibiotics have a wide tissue distribution, but doxycycline is more lipid soluble than other tetracyclines, providing greater tissue penetration and a longer half-life (Shaw and Rubin 1986).…”
mentioning
confidence: 99%